IMPLEMENTASI SISTEM CERDAS PENGONTROL DAN MONITORING MCB PANEL LISTRIK PLN SECARA TERPUSAT PADA LABORATORIUM IIB DARMAJAYA - Ari Widiantoko; Bayu Nugroho (IIB Darmajaya, 2019)
A control system is a very important aspect in modern technology. This is a interconnection of the components in the connected or associated in such a way as to a direct order or regulate itself and another system. In IIB darmajaya electric system is still done manually , thus that personnel must make building of life and death MCB ( miniature circuit breakers and officials did not can on the monitoring of the MCB will are in a on or off. Based on these problems so there should have a system that could be implemented centrally and also made aimed to ease the users or officers can control and on the monitoring an electrical device from a distance. The design process made system made up of several components of them mikrokontroler arduino that serves as control , CT (Current Transformer) censorship as detecting an electric current , ethernet shield as a liaison tissue between the computer by arduino and relay (Magnetic Contactor) as a switch. Thus, the result of this research is the control system and on the monitoring an electrical device on MCB centrally. Thus the building only will no longer around to check mcb installed at every building as the use of electricity in line with the needs so as to diminish electricity consumption will have.Keywords : Microcontroler Aduino, Ethernet Shield, System Control, MCB